2021
DOI: 10.1002/ehf2.13252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of HeartLogic™ compared with standard care in heart failure patients

Abstract: Aims The implantable cardiac defibrillator/cardiac resynchronization therapy with defibrillator-based HeartLogic ™ algorithm has recently been developed for early detection of impending decompensation in heart failure (HF) patients; but whether this novel algorithm can reduce HF hospitalizations has not been evaluated. We investigated if activation of the HeartLogic algorithm reduces the number of hospital admissions for decompensated HF in a 1 year post-activation period as compared with a 1 year pre-activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…In previous works, the ability of HeartLogic to detect actionable HF events has been demonstrated, facilitating effective remote management [ 25 , 26 , 27 , 28 , 29 ]. In the context of the COVID-19 pandemic, the multisensor diagnostic platform was used effectively to facilitate the remote assessment of patient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, the ability of HeartLogic to detect actionable HF events has been demonstrated, facilitating effective remote management [ 25 , 26 , 27 , 28 , 29 ]. In the context of the COVID-19 pandemic, the multisensor diagnostic platform was used effectively to facilitate the remote assessment of patient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…117 Particular algorithms can, for example, integrate a multivariate index of heart sounds, respiration rate, thoracic impedance, and physical activity to attempt to predict the degree of congestion, with early evidence of association with fewer HF hospitalizations. 118 However, the utility of this technology in differentiating HF from COVID-19related lung injury yielded mixed results. 119,120 The post-pandemic world of remote monitoring and telemedicine for patients with HF is likely to include all forms of care including virtual, in-person, and remote assessments.…”
Section: Challenges and Innovations In Hf Care Delivery During The Pandemicmentioning
confidence: 99%
“…Recent data have also suggested that activation of the multi-sensor algorithm might result in a significant reduction in hospitalizations for decompensated HF. 15 Recently, Calò et al 9 analyzed the alert management strategies adopted at 22 centers and found that, when clinical actions were undertaken in response to alerts, the rate of HF events was lower. In their experience, actions consisted mainly of drug adjustments.…”
Section: Discussionmentioning
confidence: 99%